Nurcholish Madjid's Multiperspective Neuroparaemiophenomenology of Love - Kao, Tzu-Jen; Anurogo, Dito; Rachman, Budhy Munawar; Ikrar, Taruna (Universitas Nahdlatul Ulama Surabaya, 2022)
Unification theory seeks to gain a comprehensive understanding of something. The goal of unification theory is to bring together multiviews on love. If “Love” is not understood from multiple perspectives, it will be difficult to understand and easy to misinterpret. This paper expresses Nurcholish Madjid's